2020
DOI: 10.1136/bmjgh-2020-003282
|View full text |Cite
|
Sign up to set email alerts
|

Shortages and price variability of essential cytotoxic medicines for treating children with cancers

Abstract: IntroductionLow-income and middle-income countries (LMICs) face the largest burden of mortality from childhood cancers with limited access to curative therapies. Few comparative analyses across all income groups and world regions have examined the availability and acquisition costs of essential medicines for treating cancers in children.MethodsA cross-sectional survey involved countries in five income groups—low-income (LIC), lower-middle-income (LMC), upper-middle-income (UMC), two high-income country groups … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…While YLDs contribute less to global DALYs, the percentage of DALYs estimated to be caused by YLDs increased with increasing SDI quintiles, ranging from 1.4% (95% UI, 1.1%-1.8%) in the low SDI quintile to 5.7% (95% UI, 4.2%-7.1%) in the high SDI quintile. This greater comparative contribution of YLDs in higher SDI settings is consistent with likely improved survival, given generally more available access to cancer screening, diagnosis, and treatment as SDI increases. Consequently, the contribution of YLDs to health loss due to cancer would be expected to be increasingly relevant to global health planning as cancer survival improves globally, and the support needs of survivors of cancer should be considered as part of comprehensive cancer control planning efforts …”
Section: Discussionmentioning
confidence: 99%
“…While YLDs contribute less to global DALYs, the percentage of DALYs estimated to be caused by YLDs increased with increasing SDI quintiles, ranging from 1.4% (95% UI, 1.1%-1.8%) in the low SDI quintile to 5.7% (95% UI, 4.2%-7.1%) in the high SDI quintile. This greater comparative contribution of YLDs in higher SDI settings is consistent with likely improved survival, given generally more available access to cancer screening, diagnosis, and treatment as SDI increases. Consequently, the contribution of YLDs to health loss due to cancer would be expected to be increasingly relevant to global health planning as cancer survival improves globally, and the support needs of survivors of cancer should be considered as part of comprehensive cancer control planning efforts …”
Section: Discussionmentioning
confidence: 99%
“…Methodologically, 15 (68.2%) studies used standardized WHO/HAI methodology, [ 14 , 16 18 , 20 , 22 26 , 30 – 34 ] 2 (9.1%) studies used adapted WHO/HAI method, [ 13 , 29 ] and the remaining 5 (22.7%) studies used other methods. [ 15 , 19 , 21 , 27 , 28 ] The mean number of essential medicines investigated was 31 (range: 5 to 121).…”
Section: Resultsmentioning
confidence: 99%
“…Most studies (21, 95.5%) were rated as low risk of bias, [ 13 27 , 29 34 ] whereas one study (4.5%) was graded as medium risk. [ 28 ] 11 studies achieved 9 points and 9 studies scored 8 points.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, there is no methodology for measuring accessibility of essential medicines specifically for children, but a number of studies have reported on the availability or price of medicines, or both 7–35. The methodologies for measuring these two important dimensions of access varied greatly between studies, as did the medicines surveyed, covering different age groups of children (eg, children under 5, children under 12 or all children and adolescents), priority diseases (anticancer medicines, cardiovascular medicines or a range of diseases) and number of surveyed medicines.…”
Section: Introductionmentioning
confidence: 99%